Pengaruh profitabilitas dan leverage terhadap return saham pada perusahaan manufaktur sektor food and beverages yang terdaftar di Bursa Efek Indonesia - Rasyid, Rosyeni; Mulyani, Gita Sri; Zulvia, Yolandafitri (Jurnal Kajian Manajemen Bisnis, 2018)
This research was conducted in order to analyze the effect of profitability as measured by ROA and Leverage as measured by DER to Return of Stock Company of Food and Beverages Manufacturing sector listed in Indonesia Stock Exchange for period 2012-2016. The population in this study are food and beverages companies listed on the Indonesia Stock Exchange in 2012-2016. The sample in this research is determined by purposive sumpling based on criteria as (1) manufacturing company of food and beverages sub sector listed in Indonesian Stock Exchange from 2012 until 2016 (2) Company that publishes complete financial report during observation period from 2012 until by 2016. (3) Companies with data leverage (DER), and profitability ratios (ROA) complete and have been processed. The sample in this research is 49. The results of this study show (1) Return On Assets (ROA) have a positive and significant effect on stock returns. (2) Debt To Equty Ratio (DER) has a negative and insignificant effect on stock returns on food and beverages companies listed in Indonesia Stock Exchange 2012-2016Keywords: Return on asset (ROA); debt to equity ratio (DER);return saham